Fish stocking as fishing management strategy and its role in delaying the management of aquatic ecosystems - López-Casas, Silvia; Restrepo-Santamaría, Daniel; Valencia-Rodríguez , Daniel; Muñoz-Duque, Sebastián; Loaiza-Santana, Alejandro; Jiménez-Segura, Luz Fernanda (Revista de Biología Tropical, 2024)
Introduction: Fish stocking has been one of the most applied management actions worldwide for managing declining fisheries. However, worldwide, technical requirements have been identified to carry out these activities and improve their effectiveness, which in the Colombian case have been included in the fishing regulations since 2017. Objective: To discuss the role of restocking as a fisheries management strategy in delaying the management of inland aquatic ecosystems. Methods: For the period 1990-2023, we searched for technical and scientific publications in electronic media, using the keywords "repoblamiento pesquero" and "fish stocking". We researched and requested fishing landings and fish restocking data from Colombia. We calculated total and by species releases for the reported systems and tested their efficiency by correlating releases with one year lag fish landings. Results: There are different terms to describe the intentional release of fish into aquatic ecosystems as a management practice. Its use might vary according to the objectives of fish releases or due to translation difficulties from English to Spanish. The origin of the practice is associated with freshwater integrity loss in which species of commercial and economic interest inhabit but does not replace the management actions of the impacted ecosystems. We found no relationship between fish releases and fish landings. Conclusions: Stocking has not been effective as a fisheries management measure, since it has been used to artificially increase fish populations impacted by low integrity of their habitats. Without real impacts on fisheries, it supports a misleading idea of action, leading us down an evasive and dilatory path of our environmental responsibilities.